KONSEP AMANAH DALAM HADIS DAN IMPLIKASINYA TERHADAP PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM - Ahmad Fatoni; Akbar Rahman; Darul Mustofa; Ayub Kumalla; Ahmad Saeful Ahyar (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the concept of amanah (trustworthiness) in the hadith of Prophet Muhammad and its implications for the professionalism of Islamic Religious Education teachers. Method: This study employed a qualitative approach using library research. Primary data were obtained from hadiths related to amanah found in authoritative hadith collections, while secondary data were collected from books, scientific articles, and relevant previous studies. Data were analyzed using a thematic hadith (maudhu'i) approach and content analysis techniques. Results: The findings indicate that the concept of amanah in hadith encompasses four main dimensions: responsibility, competence, integrity, and exemplary conduct. These dimensions are closely related to the pedagogical, professional, social, and personal competencies that form the standards of teacher professionalism. Amanah serves as an ethical and spiritual foundation that encourages teachers to perform their duties professionally, enhance their competencies, maintain integrity, and provide positive role models for students. Novelty: This study positions amanah in hadith as the primary foundation of Islamic Religious Education teacher professionalism. The findings demonstrate that amanah is not merely a component of character education but a central concept underlying all aspects of teacher professionalism from the perspective of Islamic education.